Chlorella-Daphnia consortium as a promising tool for bioremediation of Nile tilapia farming wastewater. Issue 9 (21st October 2022) - Campos, Clarissa Vilela Figueiredo da Silva; Oliveira, Carlos Yure B.; dos Santos, Elizabeth Pereira; de Abreu, Jéssika Lima; Severi, William; da Silva, Suzianny Maria Bezerra Cabral; Brito, Luis Otavio; Gálvez, Alfredo Olivera
ABSTRACT: The objective of this study was to investigate the effluent treatment from Nile tilapia farming in a biofloc system with a consortium of microalgae ( Chlorella vulgaris ) and zooplankton ( Daphnia similis) . Thus, integrated cultures of C. vulgaris and D. similis were performed in two forms of wastewater treatment: sedimentation (S) and non-sedimentation (NS), in four different salinities (1, 2, 3 and 4 g L −1 ). Water quality, growth of D. similis, behaviour of C. vulgaris, efficiency of removal of nitrogen compounds, orthophosphate, and total suspended solids (TSS) were measured. D. similis had higher density in 3NS ( p < 0.05), while population die-off occurred in 4S and 4NS. The 2S and 1NS combinations stood out in bioremediation, achieving removal of up to 70.37% nitrate, 75.74% orthophosphate, and 90.74% TSS. 2S and 3S cultures became self-sufficient from day 21. Thus, the Chlorella-Daphnia consortium using 3NS allowed better production of D. similis, whereas salinities 2 g L −1 (S) and 1 g L −1 (NS) provided better bioremediation, and the use of S wastewater improved the sustainability of the system. These results contribute to a better evaluation of cultures in consortia of organisms for the treatment of aquaculture wastewater and the production of live feed for aquaculture. Highlights: Four salinities and two forms of biofloc wastewater processing were evaluated. Salinity 2 and sedimentation of biofloc wastewater showed better bioremediation. Salinity 3 and non-sedimentation of biofloc wastewater had better D. similis growth. C. vulgaris could grow in biofloc wastewater even with Daphnia predation. Chlorella-Daphnia consortium is an option for bioremediation and live food production. GRAPHICAL ABSTRACT: UF0001